Wnt-GSK3β/β-Catenin Regulates the Differentiation of Dental Pulp Stem Cells into Bladder Smooth Muscle Cells - Wenkai Jiang; Diya Wang; Amr Alraies; Qian Liu; Bangfu Zhu; Alastair J. Sloan; Longxing Ni; Bing Song (Hindawi Limited, 2019)
Smooth muscle cell- (SMC-) based tissue engineering provides a promising therapeutic strategy for SMC-related disorders. It has been demonstrated that human dental pulp stem cells (DPSCs) possess the potential to differentiate into mature bladder SMCs by induction with condition medium (CM) from bladder SMC culture, in combination with the transforming growth factor-β1 (TGF-β1). However, the molecular mechanism of SMC differentiation from DPSCs has not been fully uncovered. The canonical Wnt signaling (also known as Wnt/β-catenin) pathway plays an essential role in stem cell fate decision. The aim of this study is to explore the regulation via GSK3β and associated downstream effectors for SMC differentiation from DPSCs. We characterized one of our DPSC clones with the best proliferation and differentiation abilities. This stem cell clone has shown the capacity to generate a smooth muscle layer-like phenotype after an extended differentiation duration using the SMC induction protocol we established before. We further found that Wnt-GSK3β/β-catenin signaling is involved in the process of SMC differentiation from DPSCs, as well as a serial of growth factors, including TGF-β1, basic fibroblast growth factor (bFGF), epidermal growth factor (EGF), hepatocyte growth factor (HGF), platelet-derived growth factor-homodimer polypeptide of B chain (BB) (PDGF-BB), and vascular endothelial growth factor (VEGF). Pharmacological inhibition on the canonical Wnt-GSK3β/β-catenin pathway significantly downregulated GSK3β phosphorylation and β-catenin activation, which in consequence reduced the augmented expression of the growth factors (including TGF-β1, HGF, PDGF-BB, and VEGF) as well as SMC markers (especially myosin) at a late stage of SMC differentiation. These results suggest that the canonical Wnt-GSK3β/β-catenin pathway contributes to DPSC differentiation into mature SMCs through the coordination of different growth factors.